Pengaruh Lingkungan Kerja, Stress Kerja, dan Motivasi Kerja terhadap Kinerja Karyawan - Putra, Yudi Prasetya (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Institut Teknologi dan Bisnis (ITB) Semarang, 2021)
This study aims to examine the effect of work environment, work stress and work motivation on employee performance. This type of research used is quantitative research. This study uses the census method, which takes all the population as research respondents. The number of respondents is 50 people and the results of the analysis using SPSS Version 20. Based on the results of the t-test data analysis, it is concluded that: (1). The work environment has a positive and significant effect on employee performance with a value of 0.003, (2). Work stress has no significant effect on employee performance with a value of 0.170. (3). Work motivation has no significant effect on employee performance with a value of 0.070. (4). Simultaneously the variables of work environment, work stress and work motivation have an effect on employee performance with the results of the f test sig value of 0.000 <0.05.